Pengaruh Proporsi Dewan Komisaris Independen dan Aktivitas Komite Audit Terhadap Risk Disclosure Index Perusahaan Farmasi yang Terdaftar BEI 2020-2024 - Rachyu Purbowati; Alya Rahmawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the influence of corporate governance mechanisms on the Risk Disclosure Index (RDI) in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. The independent variables tested include the Proportion of Independent Commissioners (DKI), Audit Committee (KA), and Frequency of Audit Committee Meetings (RKA). The population in this study was all pharmaceutical companies on the IDX with a sampling technique using purposive sampling, resulting in a total of 50 observation data. The data analysis method used multiple linear regression analysis processed through the SPSS program. The partial test results showed that the DKI, KA, and RKA variables had no significant effect on the Risk Disclosure Index with significance values ​​of 0.648, 0.441, and 0.336, respectively. The Coefficient of Determination ($R^2$) value showed 0.023, which indicated that the ability of the independent variables to explain variations in risk disclosure was only 2.3%, while the remaining 97.7% was influenced by other factors outside the model. The research conclusion shows that governance mechanisms in the pharmaceutical sector are not optimal in encouraging transparency in risk disclosure.